Deformation kinetics of coarse-grained and ultrafine-grained commercially pure Ti - Blum, Wolfgang; Li, Yujiao; Breutinger, Falk (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2007)
The elevated temperature deformation kinetics of ultrafine-grained (UFG) Ti of commercial purity (grade 2) produced by equal channel angular pressing (ECAP) at elevated temperature was measured and compared to that of coarse-grained (CG) Ti. Like CG Ti, the UFG Ti exhibits dynamic strain aging effects related to transition between jerky glide of dislocations without solute cloud and viscous glide with cloud. In the jerky region the yield stress of UFG Ti is distinctly enhanced compared to CG Ti. The steady state deformation resistances of CG and UFG Ti are not significantly different. The jerky → viscous transition results in a relative maximum of deformation resistance as function of strain, which is explained by the opposing effects of cloud formation and coarsening of dislocation structure. The high content of grain boundaries and dislocations in the initial state of UFG Ti stabilizes the material against break-away of dislocations from their clouds. © 2006 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Deformation kinetics; Dislocation model; Dynamic strain aging; Solute clouds; Transition; UFG Ti